Potential role of lipophagy impairment for anticancer effects of glycolysis-suppressed pancreatic ductal adenocarcinoma cells - Zhiheng Zhang; Haruna Aoki; Keitaro Umezawa; Joshua Kranrod; Natsumi Miyazaki; Taichi Oshima; Takuya Hirao; Yuri Miura; John Seubert; Kousei Ito; Shigeki Aoki (Cell Death Discovery, 2024)
Abstract Although increased aerobic glycolysis is common in various cancers, pancreatic ductal adenocarcinoma (PDAC) cells can survive a state of glycolysis suppression. We aimed to identify potential therapeutic targets in glycolysis-suppressed PDAC cells. By screening anticancer metabolic compounds, we identified SP-2509, an inhibitor of lysine-specific histone demethylase 1A (LSD1), which dramatically decreased the growth of PDAC PANC-1 cells and showed an anti-tumoral effect in tumor-bearing mice. The growth of glycolysis-suppressed PANC-1 cells was also inhibited by another LSD1 inhibitor, OG-L002. Similarly, the other two PDAC cells (PK-1 and KLM-1) with suppressed glycolysis exhibited anticancer effects against SP-2509. However, the anticancer effects on PDAC cells were unrelated to LSD1. To investigate how PDAC cells survive in a glycolysis-suppressed condition, we conducted proteomic analyses. These results combined with our previous findings suggested that glucose-starvation causes PDAC cells to enhance mitochondrial oxidative phosphorylation. In particular, mitochondrial fatty acid metabolism was identified as a key factor contributing to the survival of PDAC cells under glycolysis suppression. We further demonstrated that SP-2509 and OG-L002 disturbed fatty acid metabolism and induced lipid droplet accumulation through the impairment of lipophagy, but not bulk autophagy. These findings indicate a significant potential association of lipophagy and anticancer effects in glycolysis-suppressed PDAC cells, offering ideas for new therapeutic strategies for PDAC by dual inhibition of glycolysis and fatty acids metabolism.